Common α-Fuzzy Fixed Point Results for Kannan Type Contractions with Application - Amer Hassan Albargi; Jamshaid Ahmad (Journal of Function Spaces)
The purpose of this paper is to utilize complex valued extended b-metric space and obtain common α-fuzzy fixed point theorems under Kannan type contractions. As application, we derive common α-fixed point results for multivalued mappings in the context of complex valued extended b-metric space.